PREVENTING DIABETIC KIDNEY DISEASE: A SYSTEMATIC REVIEW OF CURRENT PHARMACOLOGICAL APPROACHES - DHARANI, B.; SEBASTIAN, STEPHY; NAZRIN, S.; A., SUBA (International Journal of Applied Pharmaceutics, 2025)
Objective: This review examines the growing global burden of Diabetic Nephropathy (DN), a major complication of Diabetes Mellitus (DM) and a leading cause of Chronic Kidney Disease (CKD) and End-Stage Renal Disease (ESRD). With diabetes rates increasing, DN presents a significant health challenge. Current treatments manage established DN, but preventive strategies targeting high-risk individuals are urgently needed. This review evaluates current and emerging therapies for DN prevention. Methods: A comprehensive literature search was conducted across multiple databases (PubMed, Web of Science, SCOPUS and others) to identify studies on the treatment and prevention of DN in DM patients. Eligible studies included Randomized Controlled Trials (RCT), cohort studies and meta-analyses published upto 2024, focusing on outcomes like albuminuria, Glomerular Filtration Rate (GFR) and ESRD incidence. Results: Current treatments, including Sodium Glucose Co-transporter 2 (SGLT2) inhibitors, Angiotensin-Converting Enzyme (ACE) inhibitors and Angiotensin Receptor Blocker (ARB), effectively reduce albuminuria and slow progression. Emerging therapies, such as antioxidants (Alpha-Lipoic Acid (ALA), Resveratrol), Mineralocorticoid Receptor Antagonists (MRA) and Endothelin Receptor Antagonists (ERA), show promise in improving kidney function and reducing inflammation. Other potential therapies targeting Oxidative Stress (OS), inflammation and fibrosis, such as Advanced Glycation End products(AGE) inhibitors and Tumor Necrosis Factor-α (TNF-α) inhibitors, have demonstrated preclinical efficacy but require further validation. Conclusion: While current therapies slow DN progression, they do not offer definitive prevention. Emerging treatments targeting oxidative stress, inflammation and fibrosis show promise in reducing kidney damage. However, challenges like side effects and long-term safety remain. Further research is needed to establish the efficacy of these therapies and develop personalized strategies for preventing DN in high-risk populations.